Conversion of soluble recalcitrant phosphorus to recoverable orthophosphate form using UV/H2O2. (September 2021) - Venkiteshwaran, Kaushik; Kennedy, Eileen; Graeber, Caitlin; Mallick, Synthia P.; McNamara, Patrick J.; Mayer, Brooke K.
Abstract: Soluble non-reactive phosphorus (sNRP), such as inorganic polyphosphates and organic P, is not effectively removed by conventional physicochemical processes. This can impede water resource reclamation facilities' ability to meet stringent total P regulations. This study investigated a UV/H2 O2 advanced oxidation process (AOP) for converting sNRP to the more readily removable/recoverable soluble reactive P (sRP), or orthophosphate, form. Synthetic water spiked with four sNRP compounds (beta-glycerol phosphate, phytic acid, triphosphate, and hexa-meta phosphate) at varying H2 O2 concentration, UV fluence, pH, and temperature was initially tested. These compounds represent simple, complex, organic, and inorganic forms of sNRP potentially found in wastewater. The efficiency of sNRP to sRP conversion depended on whether the sNRP compound was organic or inorganic and the complexity of its chemical structure. Using 1 mM H2 O2 and 0.43 J/cm 2 (pH 7.5, 22 °C), conversion of the simple organic beta-glycerol phosphate to sRP was 38.1 ± 2.9%, which significantly exceeded the conversion of the other sNRP compounds. Although conversion was achieved, the electrical energy per order (EEO ) was very high at 5.2 × 10 3 ± 5.2 × 10 2 kWh/m 3 . Actual municipal wastewater secondary effluent, with sNRP accounting for 15% of total P, was also treated using UV/H2 O2 . No wastewater sNRP to sRP conversion was observed, ostensibly due to interference from wastewater constituents. Wastewater utilities that have difficulty meeting stringent P levels might be able to target simple organic sNRP compounds, though alternative processes beyond UV/H2 O2 need to be explored to overcome interference from wastewater constituents and target more complex organic and inorganic sNRP compounds. Highlights: Soluble non-reactive phosphorus (sNRP) was the 2nd largest fraction of wastewater P. sNRP's chemical structure affects its conversion to sRP using advanced oxidation. Conversion of simple organic sNRP using UV/H2 O2 was greater than other compounds. Wastewater constituents negatively affect UV/H2 O2 conversion of sNRP to sRP.